Geography book 2 - Dunn, Cameron; Adams, Kim; Chiles, Michael (Hodder Education, 2021)
Cramming all new-case studies, new geographic data and reams of new questions, this new Pearson Edexcel A-level Geography student book will capture imaginations as it travels around the globe. This new book will help your students develop the geographical skills and knowledge they need to succeed. It has been written by our expert author team and structured to provide support for learners of all abilities. The book includes: · Activities and regular review questions to reinforce geographical knowledge and build up core geographical skills · Clear explanations to help students to grapple with tricky geographical concepts and grasp links between topics · Case studies from around the world to vividly demonstrate geographical theory in action · Exciting fieldwork projects that meet the fieldwork and investigation requirements This student book is supported by digital resources on our new digital platform Boost, providing a seamless online and offline teaching experience.